Desenho tecnológico interativo do blog de moda de RUA RIO ETC - Ribeiro, Helena Gabrielle Souza (2015)
This research investigates, based on modern social dynamics, the construction of the concept of Technological Design Interactive Rio Etc blog, in order to broaden the conceptions of design as an image it projects, communicates and can be constantly reinterpreted through a perspective interdisciplinary, seeking to recognize design as design, purpose and intent, then, is beyond its instrumentality and representation of human action through a pencil and a sheet of paper. Among the goals, I try to identify through the web interface analysis, while visual image, as shown blog design Rio Etc by proposing a street fashion concept on the Internet. I seek to do so, to express how is the formation of a Technology Interactive Design; attentive to fashion's image as a mediating element between man and culture in the digital environment and point out the street-style as contemporary phenomenon in tribalisation of subjects inserted in the group that plans and produces photographic images to the blog (main content of posts Rio Etc) and portrays the street fashion as a lifestyle, and spread this idea over the internet through the blog tool. Based on this, the Comprehensive Sociology appears to support, in the Interdisciplinary methodology, the unfolding of man as a social being who participates in the cyberculture as a producer designs and puts them at the disposal of Internet users. In this qualitative research, we present an overview of images collected in Rio Etc blog over two years of research, focused on illustrative presentation of archived records in the blog since 2007 (rise of the Rio electronic diary), incorporating the text images that best could set the observed phenomena. I emphasize that the concept of street-style produced by Rio Etc does not include the capital in its territorial and economic diversity, but rather part of a cutout on the street fashion that moves specifically for the south of the city.